The Effect of Corporate Tax, Managerial Ownership, and Company Growth on Dividend Payments - Futri, Jayanti Ega; Randa, Gusti; Nasution, Yaman Udayef; Saputra, Alex (Golden Ratio of Taxation Studies, 2025)
This study aims to empirically examine the effect of corporate tax, managerial ownership, and company growth on dividend payments. The research was conducted on manufacturing companies in the chemical industry sub-sector listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. This study employed a descriptive associative method using secondary data. The samples were selected using a purposive sampling technique, resulting in 80 observations from 16 companies over five years. Data analysis was conducted using Microsoft Excel and EViews 9, including descriptive statistics to describe data characteristics, model fit tests to assess model suitability, classical assumption tests to ensure data validity, coefficient of determination (R²) to measure model explanatory power, and panel data regression to test hypotheses. The F-test results show that corporate tax, managerial ownership, and company growth simultaneously significantly affect dividend payments. The t-test results indicate that managerial ownership and company growth partially have a positive and significant impact on dividend payments, while corporate tax does not have a significant effect. This finding suggests corporate tax policies may not influence companies' dividend distribution decisions.